2012
DOI: 10.1542/peds.2011-1704
|View full text |Cite
|
Sign up to set email alerts
|

Late Intravenous Immunoglobulin Treatment in Patients With Kawasaki Disease

Abstract: IVIG treatment ≥10 days after illness onset achieves resolution of inflammation but was found to be insufficient for preventing CALs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 32 publications
5
41
1
1
Order By: Relevance
“…Various risk factors for cardiac sequelae of KD have been reported: male gender, 23 – 26 infants, 23 , 2729 older children, 23 , 29 , 30 recurrent cases, 31 late IVIG treatment, 32 and refractoriness to initial IVIG treatment. 28 , 31 , 3336 In the studies that reported that patient age was a risk factor for coronary artery damage in KD, the authors discussed the late start of initial IVIG treatment resulting from a late diagnosis and/or incomplete presentation, as part of their interpretation of the contribution of patient age.…”
Section: Introductionmentioning
confidence: 99%
“…Various risk factors for cardiac sequelae of KD have been reported: male gender, 23 – 26 infants, 23 , 2729 older children, 23 , 29 , 30 recurrent cases, 31 late IVIG treatment, 32 and refractoriness to initial IVIG treatment. 28 , 31 , 3336 In the studies that reported that patient age was a risk factor for coronary artery damage in KD, the authors discussed the late start of initial IVIG treatment resulting from a late diagnosis and/or incomplete presentation, as part of their interpretation of the contribution of patient age.…”
Section: Introductionmentioning
confidence: 99%
“…However, overall outcomes remained worse, with 27% of patients having coronary artery lesions in the convalescent phase as compared to 1% in the early IVIg group. 32 Among patients who did not have coronary artery lesions before IVIg therapy, the rate of developing lesions in the acute phase was similar regardless of timing of IVIg; however, in the convalescent phase, late IVIg patients still fared worse (5% vs. 1% with coronary artery lesions). 32 In contrast, using the same database, retrospective comparison of KD patients treated before the 5th day of illness to patients treated conventionally between days 5 and 9 demonstrated that early treatment was more likely to result in need for additional IVIg therapy (16% vs. 9%).…”
Section: Timing Of Therapymentioning
confidence: 93%
“…A case-control study using a Japanese national database compared 75 patients treated with IVIg between days 11 and 20 of illness, with pair-matched controls treated between days 4 and 8. 32 Approximately half of the late IVIg group had coronary artery lesions at the time of therapy, and, of these, half normalized in the convalescent phase (> 1 month after onset). However, overall outcomes remained worse, with 27% of patients having coronary artery lesions in the convalescent phase as compared to 1% in the early IVIg group.…”
Section: Timing Of Therapymentioning
confidence: 97%
“…2 IVIG more than 10 days after the onset of fever may be less effective. 3 Atypical clinical features of Kawasaki disease can easily be overlooked or misinterpreted. Here we describe the unusual presentation of Kawaski disease with acute and profound sensorineural hearing loss.…”
Section: Introductionmentioning
confidence: 99%